Mining Class Association Rules in Distributed Datasets - Thuy Loan, Nguyen Thi; Tuấn, Đỗ Trung; Ngự, Nguyễn Hữu (Journal of Computer Science and Cybernetics, 2014)
This paper proposes a method for mining class association rules in distributed datasets using peer-to-peer network. This method utilizes the computing performance of PCs in the network to process the local information at each site, and then only transfers the information of item sets that their supports satisfying the minimum support threshold to the mining site. Therefore, the proposed method can reduce the memory usage than that of transferring all dataset’s information to the mining site.